Different responses of incidence-weighted and abundance-weighted multiple facets of macroinvertebrate beta diversity to urbanization in a subtropical river system. (October 2022) - Liu, Zhenyuan; Heino, Jani; Soininen, Janne; Zhou, Tingting; Wang, Weimin; Cui, Yongde; Chen, Yushun; Li, Zhengfei; Zhang, Junqian; Xie, Zhicai
Highlights: Beta diversity weighted by incidence vs abundance data varied differently along urbanization gradient. Richness difference contributed more to beta diversity weighted by abundance than incidence data. Stochasticity was more dominant in shaping beta diversity weighted by abundance than incidence data. Homogenization studies should consider the roles of rare and abundant taxa. Abstract: Urbanization is one of the major drivers of biotic homogenization (i.e., decrease in beta diversity) in freshwater systems. However, only a few studies have simultaneously examined how urbanization affects multiple facets (i.e., taxonomic, functional and phylogenetic) of beta diversity and its underlying ecological drivers in urban river macroinvertebrates. Here, we distinguished the patterns and ecological mechanisms of multiple facets of macroinvertebrate beta diversity weighted by incidence and abundance data in a subtropical river system with a distinct urbanization gradient. We also investigated how total beta diversity patterns stem from replacement versus richness difference among sites. Our results showed that taxonomic and phylogenetic beta diversities weighted by incidence data were primarily driven by replacement of taxa, whereas the richness difference contributed more to multiple facets of beta diversity based on abundance data. Furthermore, multiple facets of beta diversity decreased with urbanization for both incidence-weighted and abundance-weighted data, but the former showed more substantial decreases. Both replacement and richness difference components contributed roughly equally to the decline of incidence-weighted beta diversity. In contrast, the losses of abundance-weighted beta diversity were mainly associated with replacement of taxa. Variation partitioning results revealed that all beta diversity measures based on incidence data were governed primarily by local and land-use variables, whereas spatial variables were more relevant in driving beta diversity weighted by abundance data. Overall, by comparing different facets and components of beta diversity weighted by incidence versus abundance data, we suggest that incidence-weighted data may be more sensitive in portraying the impacts of urbanization on macroinvertebrate diversity. This likely resulted from the fact that incidence-weighted data shows the importance of rare taxa in shaping homogenization induced by urbanization.